The Multinational Corporation as a Political Actor: ‘Varieties of Capitalism’ Revisited - Detomasi, David (Journal of business ethics, 2015)
This paper argues that the literature examining the role that MNCs play in ‘political CSR’—an emerging area of management research concern—can be enhanced by more a fulsome examination of the ‘varieties of capitalism’ that currently exist in the global economy. We argue that the willingness and capacity of a particular MNC to participate in governance activity—which we broadly equate to political CSR—are contingent, at least in part, upon the national systems of government-business relations present in its home market. We argue that the decisions MNCs make in terms of whether and how to participate in governance are predicated in part on the domestic system of business-government relations out of which they emerge. The paper then asserts that our current conceptions of political CSR are limited, because they do not take fully into account the increasingly important corporate form of statism, in which home governments maintain a large ownership position in the country’s MNCs, even as they expand abroad. We posit that a key question this reality poses is whether such companies will reinforce established patterns of ‘political CSR’, whether they will challenge those established patterns, or whether some mutual adaptation will occur. We conclude the article with some suggestions for how this question might be explored in future work by interested scholars.